‘Transmigrasi Ilmu’: Dari Dunia Islam ke Eropa - Syamsuddin Arif (Universitas Darussalam Gontor, 2010)
It has been a sad fact that whilst the ancient Greco-Roman civilization and the so-called Renaissance have always received high praise, the period in between, popularly known as the Dark Ages, is highly obscured or just ignored. These intermediating centuries are the missing link in the history of science and civilization, when most decisive scientific inventions were made, and the foundations of modern civilisation were laid, with scholarly, literary and scientific works in their thousands, artistic creativity, great architecture, huge libraries, hospitals, universities, mapping of the world, the discovery of the sky and its secrets, and much more. It was the time when al-Biruni, al-Khwarizmi, alIdrisi, al-Razi, Ibn Sina, Ibn al-Haytham, al-Ghazali, al-Jazari and other Muslim luminaries shone on the Dark Ages. This article aims to highlight the fact that the modern Western civilization owes much to the Muslims, who did not only inherit and preserve the ancient learning but modified and developed it. It is the Muslim legacy that paved the way for the revival and enlightenment of Europe in the 15th and subsequent centuries.